Kritik ‘Alî Harb terhadap Pembacaan Teks - Asy'ari, Bashri (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2012)
‘Alî Harb, one of the contemporary Muslim thinkers, whit a philosophy background, also crushed the renewal through hermeneutic methods and gather it with the French treasury to discover Islam groundede which appropriate with the development period and history. This paper attempts to peer into the mind of hermeneutics of ‘Alî Harb and its implications for the world of Islamic thought. And it is found a result that ‘Alî Harb understand the text as a symbol and each symbol can not be abstracted the reality completely. He tried to photograph the forgotten side of the developing ideas. Therefore howefer what he did is a valuable contribution in the treasures of Islamic thought.